Skin cooling and force replication at the ankle in healthy individuals: A crossover randomized controlled trial - Dos Santos Haupenthal D.P.* (2015)
© by the National Athletic Trainers' Association, Inc.Context: Proprioception of the ankle is determined by the ability to perceive the sense of position of the ankle structures, as well as the speed and direction of movement. Few researchers have investigated proprioception by force-replication ability and particularly after skin cooling. Objective: To analyze the ability of the ankle-dorsiflexor muscles to replicate isometric force after a period of skin cooling. Design: Randomized controlled clinical trial. Setting: Laboratory. Patients or Other Participants: Twenty healthy individuals (10 men, 10 women; age=26.8 ± 5.2 years, height=171 ± 7 cm, mass = 66.8 ± 10.5 kg). Intervention(s): Skin cooling was carried out using 2 ice applications: (1) after maximal voluntary isometric contraction (MVIC) performance and before data collection for the first target force, maintained for 20 minutes; and (2) before data collection for the second target force, maintained for 10 minutes. We measured skin temperature before and after ice applications to ensure skin cooling. Main Outcome Measure(s): A load cell was placed under an inclined board for data collection, and 10 attempts of force replication were carried out for 2 values of MVIC (20%, 50%) in each condition (ice, no ice). We assessed force sense with absolute and root mean square errors (the difference between the force developed by the dorsiflexors and the target force measured with the raw data and after root mean square analysis, respectively) and variable error (the variance around the mean absolute error score). A repeated-measures multivariate analysis of variance was used for statistical analysis. Results: The absolute error was greater for the ice than for the no-ice condition (F1,19 = 9.05, P = .007) and for the target force at 50% of MVIC than at 20% of MVIC (F1,19 = 26.01, P < .001). Conclusions: The error was greater in the ice condition and at 50% of MVIC. Skin cooling reduced the proprioceptive ability of the ankle-dorsiflexor muscles to replicate isometric force.